Interpretable Prediction of Dual-Medium Tight Sandstone Reservoir Types of the Sichuan Basin: A Multi-ensemble Learning Approach for Imbalanced Data Optimization - Jiarui Zhang; Dali Yue; Wurong Wang; Linbo Qu; Yali Liu; Wei Li; Wujun Jin; Jialin Fu (Natural Resources Research, 2026)

Transformation and transport: Polyvinyl chloride microplastics modulate fipronil accumulation and toxicity in zebrafish - Long Fu; Jing Yu; Kunting Li; Peibin Xu; Keran Xu; Lei Mai; Dali Wang; Huizhen Li; Jing You; Eddy Y. Zeng (Journal of Environmental Sciences, 2026)

2-Aminoethoxydiphenyl borate induces arrhythmias via Cx43-S282 dephosphorylation - Hongjie You; Lingxi Zhang; Yimeng Zhang; Zhiping Fu; Dali Luo (In Vitro Cellular & Developmental Biology - Animal, 2026)

Elevational trends of root traits for alpine grassland are weakly dependent on grazing-related degradation - Chen Wei; Dali Chen; Cunzhi Jia; Xiaohua Zhao; Xiuzhen Fu; Ze Huang; Ying Liu; Xiaowen Hu (Soil and Tillage Research, 2025)

Transgenerational plasticity of Elymus nutans was regulated by multiple factors and not directly related to within-generational plasticity - Cunzhi Jia; Dali Chen; Xiaohua Zhao; Xiuzhen Fu; Xiaowen Hu (Plant and Soil, 2025)

The BCM1-EGY1 module balances chlorophyll biosynthesis and breakdown to confer chlorophyll homeostasis in land plants - Dali Fu; Hanlin Zhou; Bernhard Grimm; Peng Wang (Molecular Plant, 2025)

Effects of erythromycin on biofilm formation and resistance mutation of Escherichia coli on pristine and UV-aged polystyrene microplastics - Xiaofeng Han; Long Fu; Jing Yu; Kunting Li; Ziqing Deng; Ruihao Shu; Dali Wang; Jing You; Eddy Y. Zeng (Water Research, 2024)

Calcium-dependent protein kinases CPK21 and CPK23 phosphorylate and activate the iron-regulated transporter IRT1 to regulate iron deficiency in Arabidopsis - Zhangqing Wang; Yanting Zhang; Yisong Liu; Dali Fu; Zhang You; Panpan Huang; Huiling Gao; Zhenqian Zhang; Cun Wang (Science China Life Sciences, 2023)

Slow decomposition and limited nitrogen release by lower order roots in eight Chinese temperate and subtropical trees - Yanmei Xiong; Pingping Fan; Shenglei Fu; Hui Zeng; Dali Guo (Plant and Soil, 2013)

Leaf traits and relationships differ with season as well as among species groupings in a managed Southeastern China forest landscape - Fu-Sheng Chen; Karl J. Niklas; Guang-Sheng Chen; Dali Guo (Plant Ecology, 2012)

Light distribution, photosynthetic rate and yield in a Paulownia-wheat intercropping system in China - Fangdong Li; Ping Meng; Dali Fu; Baoping Wang (Agroforestry Systems, 2008)

The Giant Pandas of the Qinling Mountains, China: a Case Study in Designing Conservation Landscapes for Elevational Migrants - Colby J. Loucks; Lü Zhi; Eric Dinerstein; Wang Dajun; Fu Dali; Wang Hao (Conservation Biology, 2003)
The giant panda ( Ailuropoda melanoleuca ), now restricted to approximately 24 montane forest areas in southwest China, is one of the world's most imperiled mammals. The Qinling Mountains in Shaanxi Province is refuge to approximately 220 pandas and is the focus of our study. Pandas in the Qinling Mountains are elevational migrants, needing both low‐ and high‐elevation montane forests to survive. The current network of nature reserves provides protection for